New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China - Cao, Chenglong; Huang, Siyao; Xu, Yongqiang; Wu, Haomin; Chen, Tianpeng; Wang, Min; Da, Wa; Fan, Xiaoling (Zootaxa, 2019)
The specimens of the family Hesperiidae collected from Tibet during 2016–2018 are identified using morphology. COI sequences of 76 individuals are newly obtained. The result of our morphological study is congruent with COI gene analyses. Maximum likehood (ML) and Bayesina inferences (BI) analyses reveal that individuals identified morphologically as the same species cluster cohesively. The minimum interspecific genetic distance is 1.7% between Halpe aucma and H. filda, and the genetic distance between conspecific individuals ranged from 0 to 0.2% for the genus Halpe. A total of 51 species are recognized, and six of them, Celaenorrhinus consanguineus Leech, 1891, Barca bicolor (Oberthür, 1896), Aeromachus propinquus Alphéraky, 1897, Pedesta bivitta (Oberthür, 1886), Baoris penicillata chapmani Evans, 1937, and Ochlodes brahma Moore, 1878, are reported from Tibet for the first time, and the last species is new to China.